A comparative analytical study on the fragility assessment of box-girder bridges with various column shapes. (15th December 2017) - Soleimani, Farahnaz; Mangalathu, Sujith; DesRoches, Reginald
Highlights: Probabilistic seismic demand models are developed for bridges with prismatic and flared columns. Sensitivity analysis is conducted on the seismic response of bridge columns with different cross-section shapes. The influence of various column shapes on developing columns' fragility curves is investigated. The effects of bridge column shapes on the bridge system fragility are identified. Abstract: Bridge columns are known as the most vulnerable components of a bridge and operate as the core substructure elements of the bridge support system. Post-earthquake evidence reveals that large deformation and extensive damage of bridge columns are linked to the force and deformation capacity of the columns. Since research on the seismic vulnerability of bridges with various column shapes is limited, this paper aims to address this deficiency by evaluating the seismic performance of a variety of common column shapes. This analytical study involves assessing circular, rectangular, and oblong-shaped columns. Each shape of the column is tested as prismatic or flared along the column height as many of the bridges, constructed after 1970 in high seismic zone areas like California, are supported by flared columns. First, the study concentrates on assessment of several different column shapes as individual elements through both monotonic and cyclic pushover analysis. Second, a complete bridge system is investigated for the impact of the cross-section shapes and column flares on the fragility assessment findings. This article deals with the seismic vulnerability assessment of box-girder types bridges. A set of numerical bridge models that accounts for geometric and material uncertainties according to the California bridge characteristics is created in OpenSees. According to the results, oblong columns display less fragility compared to the other column shapes. The comparison of the seismic analysis for prismatic and flared columns shows the vulnerability of flared columns. The findings indicate that neglecting the effect of column shapes on the bridge fragilities leads to an unreliable estimation of the seismic risk and associated losses.